An annotated checklist of Lauraceae in Bangladesh - Ara, Hosne; Mia, Md Manzur-ul-Kadir; Khan, Bushra (Bangladesh Journal of Plant Taxonomy, 2007)
A preliminary report on the species of the Laurel family in Bangladesh is presented in this paper. In Bangladesh, the family is represented by 13 genera and 46 species. Updated nomenclature with synonyms, local and English names, flowering and fruiting time, diagnostic characteristics, geographical distribution and occurrence within Bangladesh have been provided under each taxon. Key words: Checklist, Lauraceae, Bangladesh DOI: 10.3329/bjpt.v14i2.533 Bangladesh J. Plant Taxon. 14(2): 147-162, 2007 (December)